The Impact of Songket Product Purchase Based on Hedonic Shopping Value and Shopping Lifestyle on MSME Songket Deli, Bandar Khalipah, Deli Serdang, North Sumatra - Pulungan, Dita Amalia; Syamsuri, Abd. Rasyid (Garuda Prestasi Nusantara Consulting, 2022)
This study intends to examine the impact of shopping at MSME Songket Deli, Bandar Khalipah, Deli Serdang, North Sumatra, based on hedonic shopping value and shopping lifestyle. Techniques for gathering data include observation, study documentation, and questionnaires. Multiple linear regression using the statistical product software solution (SPSS) application is the research analysis method. The 80 customers of the Songket Deli SMEs make up the research population. This study's sampling method, known as quota sampling, draws a sample from the total population. The study's findings demonstrate that the hedonic shopping value has an impact on consumers' decisions to buy Songket products with a tcount (9.584) value, which is a positive and significant finding (1.991). Shopping Lifestyle have a positive and significant impact on the decision to buy Songket goods with a tcount (3.437) value (1.991). With a value of Fcount (172.857), hedonic shopping value and shopping lifestyle have a positive and significant impact on product purchases (3.114). The coefficient of determination is 90.4%, leaving 18.2% unaccounted for.